Role of Cultural Heritage in the Development of Gastronomy Tourism in the Rural Area: Case of the Vipava Valley - Pipan, Anja; Gačnik, Aleš (Agricultura Scientia, 2021)
Food is a reflection of natural resources, social, economic and cultural development, which is why specific features develop in cuisine, nutrition and technology. Dishes become typically territorial because of the terroir that shapes the characteristics of the local dishes and ingredients. When planning a proper gastronomic tourism offer for the requirements of the modern tourist, it is essential to base the gastronomy on everything that is given to us by both modern cultural influences and those from the past. The research focuses on gastronomy and cuisine as interpretive tools for learning about the cultural heritage of the Vipava Valley. Based on existing theoretical findings, we examined the potential of gastronomic tourism and the role of heritage in it through semi-structured interviews with experts from various fields related to Vipava gastronomy or material and non-material cultural heritage. The findings of the interviews were confirmed by analyzing three cases from the local environment. Consolidation and upgrading of gastronomy tourism of the Vipava Valley primarily depends on the stimulating economic environment, respect for the heritage itself and individual innovations. Sustainable development of the destination is based on a strong identity of the local people and is connected with rich natural resources and the heritage of producing and processing of safe, seasonal and high-quality raw materials. The research has confirmed the great role of nature in shaping the cultural heritage in the rural areas.